2021
DOI: 10.3390/cancers13215266
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Carcinoma in Childhood: A Systematic Review

Abstract: Adrenocortical tumors are rare in children. This systematic review summarizes the published evidence on pediatric adrenocortical carcinoma (ACC) to provide a basis for a better understanding of the disease, investigate new molecular biomarkers and therapeutic targets, and define which patients may benefit from a more aggressive therapeutic approach. We included 137 studies with 3680 ACC patients (~65% female) in our analysis. We found no randomized controlled trials, so this review mainly reflects retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 174 publications
(458 reference statements)
4
18
0
1
Order By: Relevance
“…In the pediatric setting, evidence for adjuvant RT is even more limited. In a recent systematic review on pACC, we demonstrated that the rate of local recurrences was higher than expected: 81% of reported relapses were due to local recurrences or lymph node metastases [10]. In contrast, local recurrences in the adult setting have been reported only in around 50-60% of patients [11].…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…In the pediatric setting, evidence for adjuvant RT is even more limited. In a recent systematic review on pACC, we demonstrated that the rate of local recurrences was higher than expected: 81% of reported relapses were due to local recurrences or lymph node metastases [10]. In contrast, local recurrences in the adult setting have been reported only in around 50-60% of patients [11].…”
Section: Introductionmentioning
confidence: 76%
“…Available information on RT from the literature is listed in Table 1. None of these were randomized controlled trials (RCTs) but retrospective analyses, with 76 patients managed with RT [10]. Additionally, we included data of 4 previous unreported patients upon receiving further information from the authors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations